The field guide - DiTerlizzi, Tony.; Black, Holly (New York Simon & Schuster Books for Young Readers, 2003)
When the Grace children go to stay at their Great Aunt Lucinda's worn Victorian house, they discover a field guide to fairies and other creatures and begin to have some unusual experiences.
In which the Grace children get acquainted with their new home -- In which two walls are explored by vastly different methods -- In which there are many riddles -- In which there are answers, although not necessarily to the right questions -- In which Jared reads a book and sets a trap -- In which they find unexpected things in the icebox -- In which the fate of the mice is discovered.
Sequel: The seeing stone.
Keywords: Fairies -- Fiction; Brothers and sisters -- Fiction; Single-parent families -- Fiction; Fairies -- Juvenile literature